The Rietveld method applied to the quantitative mineralogical analysis of some soil samples from Argentina - Zabala, Stella M. (2007)
The mineralogical quantification of soils species is mainly obtained by analysis of X-ray diffraction (XRD) patterns. The classic method, for these analyses, is limited to semi quantitative determinations due to the overlapping of different specie’s peaks and processes of absorption of the constituents, the wide range of particle size distribution, etc. The use of the Rietveld method for XRD quantitative analysis, in mixtures of minerals, has allowed to improve the accuracy of the quantitative results and to extend it to complex systems, as soils, transforming it in a meaningful tool for soils investigation. In this work, quantitative results obtained by the application of classic and Rietveld methods, are compared in different soils samples from Argentina. A set of mixtures of minerals with similar composition to three studied samples, was also quantified by Rietveld method, with absolute error lower than 3%. Obtained results indicate that quantitative analysis by Rietveld method, can improve the results found by XRD classic method and may be used for the quantitative determination of soil minerals.